Alkaline treatment on kenaf fiber to be Incorporated in unsaturated polyester - Muhammad, Arbanah; Rashidi, Ahmad Ramli; Sanusi, Salmi Nur Ain; Sayed Jamaludin, Sayed Jamaludin (Asian Research Publishing Network (ARPN), 2010)
This study investigates the improvement of mechanical characteristics, including tensile strength, tensile modulus, flexural strength, and flexural modulus, of kenaf fiber incorporated into unsaturated polyester by alkaline treatment. Different concentrations of 2%, 4%, 6%, and 8% NaOH were applied to kenaf fiber mats. The optimal NaOH concentration was then selected for further analysis of tensile strength, tensile modulus, flexural strength, and flexural modulus. Scanning Electron Microscopy (SEM) was utilized to observe the morphological changes in the kenaf fiber. SEM images of treated and untreated kenaf revealed significant differences, with the treated fiber surface appearing rougher. The modification of the fiber by sodium hydroxide effectively softened the fiber surface. Results indicate that the tensile strength, tensile modulus, flexural strength, and flexural modulus increased with increasing NaOH concentration. Overall, the findings from this study demonstrate that alkaline treatment effectively improved the mechanical characteristics of kenaf fiber incorporated into unsaturated polyester.